Sandra Flunger speaks about Swiss team preparation for Milano Cortina 2026 - Sattlecker, G. (Journal of Biathlon Coaching, 2024)
Sandra Flunger is one of a few female coaches in the Biathlon World Cup. From 2013 to 2016, she coached the Women´s National Team of Austria. In 2018, Flunger became the Women´s Head Coach in Switzerland. With Selina Gasparin, Lena Häcki & Co., Flunger achieved numerous top results in the World Cup, at World Championships, and at Olympic Games. In our interview, Sandra Flunger speaks about the preparation of Team Switzerland for the home World Championships in Lenzerheide and the Olympic Games in Antholz. She also talks about her role as a female coach in the male-dominated World Cup circuit.